Effect of previous hamstring injury and limb dominance on kicking biomechanics in elite female soccer players - Navandar, A.; Garcia, C.; Veiga, S.; Torres, G.; Chorro, D.; Navarro, E. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The hamstring injury is one of the most common injuries occurring in soccer. The purpose of this study was to identify the effect of a previous hamstring injury and limb dominance on the kicking pattern of elite female soccer players. 14 players belonging to a top first division soccer team volunteered to take part in the study. They were asked about their injury history and leg dominance in a questionnaire, and they performed 5 instep soccer kicks with either limb into a target 7m away. The results showed that limb dominance had no effect on the kicking pattern in elite players. Significant differences were found in the maximum hip angular velocity while kicking with a previously injured limb as compared to a previously uninjured limb. This indicates that rehabilitation programs probably should treat the injury differently in female soccer players.